An Energy Efficiency Indicator and Grading of Shell-and-Tube Heat Exchangers. (January 2020) - Chen, Kelei; Qi, Guoli; Liu, Xueming; Zhang, Jianfei; Qu, Zhiguo
Abstract: The shell-and-tube heat exchanger is the most commonly used heat exchange equipment in the industry. Whether shell-and-tube heat exchangers are energy-saving is of great significance for the efficient using of energy. Therefore, the corresponding evaluation system and index are needed for evaluating the heat transfer process in the shell-and-tube heat exchanger. In this paper, based on Kern method, the energy efficiency evaluation index of shell-and-tube heat exchanger suitable for oil-water working medium is derived. And the relevant database is used to obtain the overall energy efficiency distribution of the industry, which is subject to the normal distribution, finally according to the overall energy efficiency distribution, the energy efficiency of the shell-and-tube heat exchanger is graded.